2009
DOI: 10.1002/joc.1959
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between monthly rainfall in northwest Iberian Peninsula and North Atlantic sea surface temperature

Abstract: This study assesses the relationship between monthly North Atlantic sea surface temperature anomalies (SSTAs) and a regional index of rainfall (NWIPR) in northwest Iberian Peninsula during the period 1951-2006 by means of the Pearson product-moment correlation. Results show a strong influence of SSTA on NWIPR in several months (February, April, May, October and December). The observed persistence of this influence up to 2-months in advance can be used for monthly predictions of rainfall. The most significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
18
0
2
Order By: Relevance
“…In a seasonal analysis of precipitation of the northwestern area of HD 1, Lorenzo et al (2008) suggested that such a positive trend in precipitation was highly correlated with South-Western and Western weather types (the first being associated with a depression to the west of Ireland with a large anticyclone over the Iberian Peninsula and the rest of Europe, and the second being characterised by depressions over the North Atlantic and the north of Europe, with high pressure over the Azores), both closely linked and positively correlated to the Eastern Atlantic pattern that, during October of the later decades, exhibited a positive trend, yielding more South-Western situations (Lorenzo et al 2008). More recently, Lorenzo et al (2010) suggested a possible relationship between precipitation in the northwestern Iberian Peninsula and sea surface temperature of the Atlantic Ocean using different temporal lags. For eastern catchments, affected by Mediterranean cyclones (Jansa et al 2001), the absence of significant tendencies is consistent with cyclone activity along the whole western Mediterranean coast (in sectors I, II and III, as defined by Bartholy et al 2009), for which no trends have been observed over the past half century (Bartholy et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a seasonal analysis of precipitation of the northwestern area of HD 1, Lorenzo et al (2008) suggested that such a positive trend in precipitation was highly correlated with South-Western and Western weather types (the first being associated with a depression to the west of Ireland with a large anticyclone over the Iberian Peninsula and the rest of Europe, and the second being characterised by depressions over the North Atlantic and the north of Europe, with high pressure over the Azores), both closely linked and positively correlated to the Eastern Atlantic pattern that, during October of the later decades, exhibited a positive trend, yielding more South-Western situations (Lorenzo et al 2008). More recently, Lorenzo et al (2010) suggested a possible relationship between precipitation in the northwestern Iberian Peninsula and sea surface temperature of the Atlantic Ocean using different temporal lags. For eastern catchments, affected by Mediterranean cyclones (Jansa et al 2001), the absence of significant tendencies is consistent with cyclone activity along the whole western Mediterranean coast (in sectors I, II and III, as defined by Bartholy et al 2009), for which no trends have been observed over the past half century (Bartholy et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…1). Therefore its rainfall has a marked seasonality (Martínez Cortizas and Pérez Alberti 2000;deCastro et al 2006;Lorenzo et al 2010). In autumn and winter the jet stream is in its lower latitudes (Gallego et al 2005;Gimeno et al 2007).…”
Section: Methodsmentioning
confidence: 97%
“…(1) X i is the monthly rainfall anomaly at one station in mm, X i is the station's mean annual rainfall in mm and N is the number of stations (Philips and McGregor 2002;Lorenzo et al 2010). SST data were retrieved from the Earth System Research Laboratory (ESRL) of NOAA, (http://www.cdc.noaa.gov/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to improve the seasonal forecast would be to identify new predictors. Previous works have shown a possible link between the Iberian precipitation and other variables like summer sea surface temperature (SST) anomalies over the North Atlantic basin (Rodríguez-Fonseca and deCastro, 2002;Lorenzo et al, 2010;Hatzaki et al, 2015), other teleconnection patterns (deCastro et al, 2006;Casanueva et al, 2014) or the Eurasian snow cover in autumn (Brands et al, 2014). The storm track activity at mid-latitudes has been related to the occurrence of extreme events (Lehmann and Coumou, 2015).…”
Section: Introductionmentioning
confidence: 99%